ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT MIDI UTAMA INDONESIA TBK - Octaviani, Yulianti; Robert Hutauruk, Martinus; Putri Milanda, Devy (OBOR: Oikonomia Borneo, 2020)
PT Midi Utama Indonesia Tbk period 2015-2018 in terms of liquidity ratios, solvency ratios, activity ratios and profitability ratios. This research method is quantitative descriptive using financial ratio analysis tools such as liquidity ratios, solvency, activity and profitability to determine the company’s financial performance. From the analysis, it is known that liquidity ratios have ratio results below the average industry ratio, solvency ratios have value ratios over the average industry ratio, activity ratios have ratios above the industry average and profitability ratios have ratios below average average industry ratio Keywords: Liquidity Ratio, Solvency Ratio, Activity Ratio, Ratio Profitability